Strategies for enhancing the initiation of cholesterol lowering medication among patients at high cardiovascular disease risk: a qualitative descriptive exploration of patient and general practitioners’ perspectives on a facilitated relay intervention in Alberta, Canada - Alexander A Leung; Hude Quan; Mingshan Lu; Todd Anderson; Kerry McBrien; Sonia Butalia; David J T Campbell; Rachelle C W Lee-Krueger; Guanmin Chen; Christopher Naugler (BMJ Open)
Objective The objective of our study was to explore the perspectives of patients and general practitioners (GPs) regarding interventions to increase initiation of cholesterol lowering medication (or statins), including a proposed laboratory-based facilitated relay intervention.Design Qualitative descriptive study using interviews and focus groups for data collection, and thematic analysis for data analysis.Setting Primary care providers and patients in Calgary, Alberta, Canada.Participants 17 GPs with primarily community-based, non-academic practices with at least 1 year of practice experience participated in semistructured interviews. 14 patients at high risk of cardiovascular disease participated in focus groups.Main outcome measures Exploration of strategies that might be used to enhance the prescription of, and adherence to statin therapy for patients with statin-indicated conditions.Results GPs proposed a variety of interventions to improve statin prescription, including electronic record audit solutions, GP directed education, and patient-oriented campaigns. Patients expressed that they may benefit from being provided access to their laboratory test results, as well as targeted education. Both parties provided positive feedback on the proposed laboratory-based facilitated relay intervention, while pointing out areas for improvement. Notably, GPs were concerned that the patient-directed component of the intervention might jeopardise therapeutic relationships, and patients were concerned about accidental disclosure of personal health information. Important considerations for the design of facilitated relay messaging should include brevity, simplicity and the provision of contact information for inquiries.Conclusions GPs and patients described several suggestions for increasing statin initiation and welcomed the proposal of a laboratory-based facilitated relay strategy. These findings support further testing of this intervention which may enhance GPs’ ability to successfully engage patients in cardiovascular risk reduction through statin therapy.